Detection of Free Amino Acids from Embelia basal - S. Kamble, Gayatri; M. Devare, Swati; M. Shah, Sapana; R. Deshpande, Nirmala; P. Salvekar, Jyoti (Asian Journal of Chemistry, 2010)
Embelia basal, a shrub from family Myrsinaceae have various medicinal values. Detection of amino acids from various extracts of Embelia basal was carried out by using different mobile phases with paper chromatographic technique. The results obtained were compared with standard amino acids in respective mobile phases. Proline and serine were found to be present in all different phases examined for fruits of Embelia basal. Total 18 amino acids were detected from different extracts of the plant. The maximum separation and detection of amino acids was observed in two specific mobile phases.